Building the surge generator model and the multi layer varistor model according to the international standards - Le Quang Trung; Quyen Huy Anh; Dinh Thi Ngoan (Journal of Technical Education Science, 2017)
This paper presented the 1.2/50ms-8/20ms combination wave generator model and the low voltage multilayer varistor model which had the needed complexity and high precision compared to the models that have been proposed previously. The generator model is used to simulate and test the response of nonlinear model of low voltage voltage multilayer varistor with standard impulses as specified in the international standards. The voltage multilayer varistor model has similar characteristics as the actual low voltage multilayer varistor of manufacturers and the necessary input parameters such as rated surge current, residual voltage and the number of voltage multilayer varistor elements in parallel. The method of determining the repeated lightning impulse currents with waveform lightning 8/20ms that voltage multilayer varistor can withstand has also been mentioned will be the basis for research to determine the lifetime of the low voltage multilayer varistor in lightning protection against indirect lighting in the low voltage network.